Family Law – Solidarity or Disarray? - Atkin, Bill (Victoria University of Wellington Law Review, 2019)
Professor Gordon Anderson and labour law are synonymous in New Zealand. Gordon has provided a vision for the future of labour law. This article is offered in a similar spirit. It was prepared for a conference on "The Future of Family Law", held in Auckland on 20 September 2018 with distinguished guest, Lady Brenda Hale, President of the United Kingdom Supreme Court. The history of family law in New Zealand is full of remarkable landmarks. Many align with the rights of various groups: children, women, Māori, those with intellectual disabilities, LGBTI+ communities and abuse victims. If we dig deeper, we find that the various parts do not make a very coherent and harmonious whole. The law is tugged in different directions. This article draws on the concept of "family solidarity", refashioned for New Zealand purposes as "family and community solidarity". Could this help develop a unifying theme? Could it form the basis for future family law reform? Developments such as legislation on child poverty reduction, the Ministry for Children and relationship property law are briefly explored.